140 - DENTISTRY IN SPORT: HOW TO ACT IN TEAM IN A SAFE MEDICINE PRESCRIPTION? (Fiep Bulletin - online, 2011)
The sportive dentistry has a very important role in the athlete's life because it provides some actions, among others, related to traumas prevention and infection control that may cause the loss or decrease of the physical performance. An aspect that has been neglected by dentist surgeons, couches and athletes referring to a safe medicine prescription.The use of substances for the increase of performance in sportsmen has been gaining strength in the last decades, and the International Olympic Committee ,trough the Anti-doping Association launches annually a list of forbidden medicines, and some of these medicines have been used routinely in the dentistry. Physical Education teachers and couches must be aware of the dentist treatments of their athletes, getting in touch with the dentist surgeons, to follow the routine of a safe medicine prescription.
Keywords: Doping; Sportive Dentistry; Multi-professional Team